Early English Poetic Culture and Meter : The Influence of G. R. Russom - Brady, Lindy; Toswell, M. J. (Book collections on Project MUSE., 2016)
"This volume develops Geoffrey Richard Russom's contributions to early English metre and style, including his fundamental reworkings and rethinkings of accepted and oft-repeated mantras."--